Kekuatan Mengikat Perjanjian Internasional dan Akibat Hukum Pelanggaran Berdasarkan Konvensi Wina 1969 - Firdhan Azhim Akbar; Ema Septariad; M. Ilham Adepioe (GLOBAL SCIENTS PUBLISHER, 2026)
International treaties are one of the primary sources of international law that serve as the basis for relations and cooperation among states. The existence of the 1969 Vienna Convention on the Law of Treaties provides a legal framework governing the formation, implementation, and termination of international treaties. In its implementation, every state is obliged to comply with the principle of pacta sunt servanda, which emphasizes that every agreement that has been validly concluded must be carried out in good faith. However, in the practice of international relations, violations of treaty obligations are still frequently found, including unilateral interpretations, delays in fulfilling obligations, and unilateral termination of treaties. This study aims to analyze the binding force of international treaties based on the 1969 Vienna Convention and to examine the legal consequences arising from violations of international treaties. This research employs a normative legal research method using statutory and conceptual approaches. The data used are secondary data obtained through library research on the 1969 Vienna Convention, books, journals, and other international law literature. The data analysis technique uses descriptive qualitative analysis to explain the relationship between the principle of pacta sunt servanda, state obligations, and the legal consequences of treaty violations. The results of this study indicate that the binding force of international treaties arises from the consent of states to be bound by a treaty through ratification, acceptance, approval, or accession as regulated in the 1969 Vienna Convention. In addition, violations of international treaties may result in legal consequences such as suspension, termination, or withdrawal from treaties in accordance with the provisions of the 1969 Vienna Convention. The implications of this study highlight the importance of strengthening state commitment in consistently implementing international obligations in order to maintain legal certainty, stability in international relations, and mutual trust among states